The Effectiveness of Promoting Mother of Pearl (MOP) Products Through the Instagram Social Media Account @mop.beauty to Beauty Enthusiasts - Arif, Artamevia Salzhabilla Putri; Zahirah, Sadira Putri; Putra, Dewantara Bima (Journal Commedies, 2024)
This study aims to analyze the level of effectiveness of product promotion for Mother of Pearl (MOP) through the social media platform Instagram @mop.beauty targeted at beauty enthusiasts. The research employs a survey method, utilizing an online questionnaire distributed to respondents from the Cosmetology Study Program at the State University of Surabaya (UNESA) class of 2024 who actively engage with beauty-related content. The questionnaire is designed to measure variables such as the frequency of viewing promotional content, perceptions of the displayed content, purchase intent, and the level of trust in the products. Collected data are analyzed using statistical software to identify relationships among these variables. The findings are expected to provide insights into how social media marketing strategies influence consumer behavior within the beauty industry and offer recommendations for brands to enhance their promotional effectiveness.